Strategy For Implementation Of The Senayan Library Management System (SLIMS) Automation System At SMK Negeri 1 Stabat (Pena Cendekia Insani, 2022)
This study discusses the library strategy of SMK Negeri 1 Stabat in the application of SLiMS automation to library services and activities, as well as the obstacles faced in carrying out the SLiMS implementation strategy in the library. This study uses a qualitative method with a descriptive approach. The results showed that the SLiMS implementation strategy in the library of SMK Negeri 1 Stabat had three stages, where the initial stage was the procurement process for the SLiMS system, the implementation stage was the implementation process in the library, and the third stage was the evaluation stage, namely assessing deficiencies in the SLiMS system. The obstacles faced are network, space, and human resources (HR) problems.